PERAN INFLUENCER MEDIA SOSIAL DAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN - Bunga Adelia Putri; Putu Nina Madiawati (Universitas Ahmad Dahlan, 2023)
A successful digital marketing strategy can lead to a company's success. Social media influencers and brand awareness are two commonly used digital marketing strategies recently. This study aims to determine how brand awareness and social media influencers influence customers' purchase decisions for the Erigo Brand. The study used Purposive sampling as the sampling technique to obtain the primary data of 100 Erigo customers. The collected data were analyzed in the SPSS program using the linear regression method. Results of the study show that social media influencers and brand awareness positively affect customers' purchase decisions for Erigo Brand.